2019
DOI: 10.1139/bcb-2018-0320
|View full text |Cite
|
Sign up to set email alerts
|

Alanyl-glutamine ameliorates lipopolysaccharide-induced inflammation and barrier function injury in bovine jejunum epithelial cells

Abstract: The aim of this study was to investigate the effects of alanyl-glutamine (Ala-Gln) on the regulation of lipopolysaccharide (LPS)-induced inflammation and barrier function in bovine jejunum epithelial cells (BJECs). BJECs were exposed (or not) to 1 μg/mL LPS for 24 h to generate a pro-inflammatory model. The cells were then treated with different concentrations of Ala-Gln (0.25, 0.5, 1.0, 2.0, or 4.0 mmol/L) to detect any regulatory effects on the inflammation and barrier function of BJECs. LPS decreased cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Interestingly, the upregulated mRNA levels of ileal IFN-γ, IL-1β , and TLR4 were abolished in E. coli- infected broilers by dietary HWG supplementation, suggesting that HWG might inhibit TLR4 signaling pathway to suppress the production of inflammatory cytokines, consequently alleviated the E. coli -induced inflammation ( Liu et al, 2017 ). Previous studies have demonstrated that functional amino acids, such as Gln and Gly, could relieve the LPS-induced intestinal injury ( Xu et al, 2018 ; Zhang et al, 2019 ). In the present study, high proportion of Gln, Gly and proline in the HWG may be responsible for the intestinal inflammatory alleviation of E. coli -infected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the upregulated mRNA levels of ileal IFN-γ, IL-1β , and TLR4 were abolished in E. coli- infected broilers by dietary HWG supplementation, suggesting that HWG might inhibit TLR4 signaling pathway to suppress the production of inflammatory cytokines, consequently alleviated the E. coli -induced inflammation ( Liu et al, 2017 ). Previous studies have demonstrated that functional amino acids, such as Gln and Gly, could relieve the LPS-induced intestinal injury ( Xu et al, 2018 ; Zhang et al, 2019 ). In the present study, high proportion of Gln, Gly and proline in the HWG may be responsible for the intestinal inflammatory alleviation of E. coli -infected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ala-Gln is usually used in enteral nutrition. Clinical and experimental investigations demonstrated that Ala-Gln increased the expression of tight junction proteins and maintained the intestinal mucosal thickness and villus height to preserve the gut barrier function (Liu et al, 1997;Zhang et al, 2019). Although Ala-Gln is widely used in various conditions, so far, it has no application reports in the field of ophthalmology.…”
Section: Introductionmentioning
confidence: 99%
“…Whether Ala-Gln has a direct anti-inflammatory effect on macrophages has not been fully investigated. A previous study has shown that Ala-Gln could enhance cell viability and inhibit the expression of inflammatory mediators in LPS-stimulated bovine intestinal epithelial cells [ 51 ]. Here, in LPS-treated RAW264.7 cells, we found that Ala-Gln significantly reduced the elevated expression of IL-6, TNF-α, and RANTES, indicating the direct anti-inflammatory effects of Ala-Gln in macrophages.…”
Section: Discussionmentioning
confidence: 99%